2016
DOI: 10.3167/jys.2016.170203
|View full text |Cite
|
Sign up to set email alerts
|

Making Friends of the Nations: Australian Interwar Magazines and Middlebrow Orientalism in the Pacific

Abstract: As travel began to massify in the aftermath of the Great War when passenger ships still regularly stopped at ports of call, and as Australia developed a sub-imperial relationship to its near Melanesian neighbors in Papua and New Guinea, the Pacific and its islands loomed large in Australian consciousness and print culture. This article employs Christina Klein's concept of "middlebrow orientalism" to examine how Australia's quality magazines, MAN and The BP Magazine, reflected an "expansive material and symboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…108 In the artsand music especiallythe interwar period is sometimes characterized as Australia's 'dullest' or 'driest'; however, much recent scholarship has demonstrated that it was indeed 'cosmopolitan, vibrant, and modernizing'. 109 While the same anti-internationalist ideas that characterized the WAP also led to censorship of imported 'obscene' and 'subversive' literature, hindering the dissemination of European modernism, there remained 'signs of a wider cultural life', from touring international artists, to the influence of European refugees, and by the 1930s commercial sponsorship of modernist art. 110 In music, the BIMS was just one organization engaging with the international.…”
Section: Internationalism and 'International' Musicmentioning
confidence: 99%
“…108 In the artsand music especiallythe interwar period is sometimes characterized as Australia's 'dullest' or 'driest'; however, much recent scholarship has demonstrated that it was indeed 'cosmopolitan, vibrant, and modernizing'. 109 While the same anti-internationalist ideas that characterized the WAP also led to censorship of imported 'obscene' and 'subversive' literature, hindering the dissemination of European modernism, there remained 'signs of a wider cultural life', from touring international artists, to the influence of European refugees, and by the 1930s commercial sponsorship of modernist art. 110 In music, the BIMS was just one organization engaging with the international.…”
Section: Internationalism and 'International' Musicmentioning
confidence: 99%